Colours of the Tijomel ceramic manufacture (1941-1992): characterisation of a set of ceramic colourants and glazed tiles from Decormel Materials Catalogue - Coutinho, Mathilda (2024)
Tijomel was considered one of the most modern ceramic manufacturers in the Iberian Peninsula in the mid-20th century. Located at Caxarias (Ourém, Portugal), this manufacturer produced diverse ceramic-based architectural materials, from common clay bricks to sophisticated modernist azulejos. Recently members of the family of the former Tijomel Manufacture owners retrieved a collection of 33 raw materials, mostly ceramic colourants. In this study, the chemical characterisation of these ceramic colourants was performed and compared with an azulejos commercial catalogue of the same manufacturer entitled Decormel Catalogue. The recovered raw materials and azulejos were investigated using a multi-analytical approach comprising h-EDXRF and μ-XRD to obtain their elemental and mineralogical composition and HSI and colourimetry to analyse their optical properties. Results provided a glimpse of the wide variety of ceramic colourants used in mid-20th century and showed that Tijomel combined the use of traditional azulejo colourants with more recent compositions.